Conglomeration of Dermal and Oral Diseases - Disorders Pertaining to Paediatric and Adult Population - An Original Research - Shunmugavelu, Karthik; Verma, Shivangi; T Ragavendran, Gowri (Journal of Neonatal Surgery, 2025)
Background: Oral cavity can be affected by a variety of disorders and many systemic disorders have wide range of manifestations in the oral cavity or mucosa. The oral mucosal lesions can be the early aspects of the disease manifestation or the only symptom of the dermatological diseases and any symptom or sign in the oral cavity should not be neglected. Materials and methods: A total of 1131 patients who came to the institute for various dermatological treatment were included in this study. The demographic details were obtained from the patient and a thorough and extensive dermatological examination was done. On examining the oral cavity, the size, site of the lesion was noted. The results of the study were entered in SPSS version 21 and descriptive statistics calculated (P < 0.05 were considered as statistically significant). The participants were informed about their oral conditions, and health education was provided Result: The patients in the age group of 25-50 years (76%) were affected most commonly that the other age group. No Gender predilection was seen, both male (49.7%) and female (50.3%) patients were equally affected. Out of 1131 patients, 237 patients along with dermatological lesions had oral mucosal lesions. One-twenty-one cases of different dermatological cases were diagnosed from 1131 patients in that 12 dermatological lesions had oral manifestations. The most common site of involvement in the oral cavity was the palate (38.3%). Psoriasis (44.3%) was the most common lesion with oral mucosal lesion which was followed by Pemphigus (31.2%) and bullous pemphigoid (10.1%). Conclusion: The significance of diagnosing the oral lesions in dermatology practice and mucocutaneous lesions in dental practice plays a pivotal role in patient management. Thus, widespread and panoramic vision of knowledge needs to be employed in diagnosing these cases in dental and dermatology practice.